Alternation of physical and functional powers of high performance female BMX cyclists during yearly training cycle - Milašius, K.; Dadeliene, R.; Tubelis, L.; Skernevicius, J. (Education. Physical training. Sport, 2012)
Research background and hypothesis. There is a lack of information on BMX cyclists` training. Information about athletes` of this cycling event training and their organism adaptation to physical loads practically does not exist in Lithuania. Consequently, it is relevant to reveal the main characteristics of alternation of Lithuanian high performance international class female cyclists` physical and functional powers. The hypothesis that physical and functional power indices between BMX cyclist and track cyclist differ is being tested. Research aim was to reveal characteristics of Lithuanian high performance female BMX cyclist`s physical and functional power indices and their alteration during yearly training cycle; to compare them to analogical data of other cycling event athletes. Research methods. Research of a Lithuanian BMX female cyclist (A) was organized in VPU Sport Science Institute in 2010-2011. Research was carried out during these yearly cycle periods: preparatory (I), competition (II), and transitional (III). Research results. Physical development indices were established and muscular power in various energy producing zones was analyzed. Maximal anaerobic alactate glycolytic capacity (MAAGC) with applied 30-s test was established as well. Functional capacity of blood circulation and respiratory system was evaluated under resting heart rate, its rate alteration after standard physical load, and after one minute recovery; under these data Roufier index was calculated. Indices of female BMX cyclist`s physical and functional powers were compared to analogical results of female sprint track cyclist - 200 m event World champion (B), and female track cyclist - 3 km pursuit event World championship bronze winner (C). Discussion and conclusions. Our analyzed BMX cyclist`s SMCP is very high and exceeds the same index of cyclists in other various specializations analyzed. However, AAMP and mixed anaerobic alactate glycolytic muscular power indices are insignificantly lower than analogical indices of one of the best World track sprinters. Elite cyclist`s (C), whose part of energy, during competition period, is produced in aerobic way, functional capacity of blood circulation system is the highest and these indices of the investigated BMX cyclist are lower than aerobic capacity of cyclist C.